1993
DOI: 10.1007/bf00023594
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a second plasma membrane H+-ATPase gene subfamily in Nicotiana plumbaginifolia

Abstract: A cDNA clone was isolated for a fourth pma gene encoding a putative plasma membrane H(+)-ATPase of Nicotiana plumbaginifolia. The sequence of the predicted 952 residue PMA4 polypeptide was compared with those of other known plant PMAs, revealing a higher identity with the Arabidopsis thaliana proteins (86-89%) than with the other three N. plumbaginifolia PMA proteins (80-82%). This supports the view that there are two pma subfamilies which probably arose from a gene duplication predating the separation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 20 publications
3
57
0
Order By: Relevance
“…The deduced amino acid sequence of LHA4 shares 75 to 98% identity with PM H+-ATPases from other plants, with greatest identity to the potato isoform PHA2 (98%) and the N. plumbaginifolia isoform PMA4 (95%). We found that LHA4 groups with the second subfamily of PM H+-ATPase genes, which also includes AHAI, AHA2, AHA3, and PMA4 (Moriau et al, 1993).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The deduced amino acid sequence of LHA4 shares 75 to 98% identity with PM H+-ATPases from other plants, with greatest identity to the potato isoform PHA2 (98%) and the N. plumbaginifolia isoform PMA4 (95%). We found that LHA4 groups with the second subfamily of PM H+-ATPase genes, which also includes AHAI, AHA2, AHA3, and PMA4 (Moriau et al, 1993).…”
Section: Discussionmentioning
confidence: 76%
“…The greatest similarity is with the potato isoform PHA2 (98%) and the N. plumbaginifolia isoform PMA4 (95%). Comparisons made over the complete sequences of PM H+-ATPases have led to the suggestion that it is appropriate to differentiate at least two subfamilies within the PM H+-ATPase gene family, with LHA1, PMA1, PMA2, and PMA3 constituting one family, and AHA1, AHA2, AHA3, and PMA4 forming the second family (Moriau et al, 1993). We have extended this analysis to include LHA4 and other recently published sequences (Fig.…”
Section: Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The expression vector, pTZ19U-gfp (Duby et al, 2001), contains the PMA4-En50 transcriptional promoter (Zhao et al, 1999), the PMA4 59 untranslated region, BglII, BamHI, and KpnI restriction sites, mGFP4 S65T (Heim et al, 1994;Haseloff et al, 1997), and the nopaline synthase transcription terminator. cDNAs coding for the Nicotiana plumbaginifolia PM H þ -ATPase isoforms PMA2 (Boutry et al, 1989), PMA3 (Boutry et al, 1989), and PMA4 (Moriau et al, 1993) were amplified by PCR to generate a fragment containing appropriate cloning sites at each end. For PMA2, the primer 59-GGGGTACCGGATCCAACAGTGTAT-GATTGCTG-39 was used to remove the stop codon and add a BamHI restriction site (underlined) at the end of the coding sequence from a PMA2 already preceded by a BamHI site (de Kerchove d'Exaerde et al, 1995).…”
Section: Plasmids and Dna Constructsmentioning
confidence: 99%
“…The two regions flanking this domain, from which the Fl and F2 oligonucleotides were derived, show 100% conservation among the cloned plant H + -ATPases, but the sequences of these domains were not determined for LHA3 through LHA7. Comparisons made over the complete sequences of plant H + -ATPases have led to the suggestion that it is appropriate to differentiate two subfamilies within the H + -ATPase gene family, with LHAl and PMA1, PMA2, and PMA3 constituting one group, and PMA4 and AHA1, AHA2, and AHA3 forming a second group (Moriau et al, 1993). Examination of the limited 69-amino acid region determined for LHAl through LHA7suggests that LHAl and LHAl belong to the first subfamily, since they are identical to PMA1, PMA2, and PMA3 over this region, and that LHA4 belongs to the second subfamily, since it is identical to PMA4, AHA1, and AHA2 and differs by one amino acid from AHA3.…”
Section: Sequence Analysismentioning
confidence: 99%